Developing Speaking Skill of Grade X Students of Senior Hight School in Palu Through Monologue Technique - Alfiani; Abd. Kamaruddin; Desrin Lebagi; Mawardin (Universitas Islam Negeri Palopo, 2025)
This research investigates the effectiveness of the monologue technique in enhancing the speaking skills of tenth-grade students at Senior High School. The study employs a quasi-experimental design, involving pre-test and post-test assessments administered to two groups of students. The experimental group was taught using the monologue technique, while the control group continued with the traditional instructional methods. By comparing the results of both groups, the research aims to identify whether the monologue technique can significantly improve students' speaking abilities. The data were analyzed using a series of statistical tests, most notably the T-test. The results indicated that the experimental group demonstrated a statistically significant improvement in their speaking performance, in contrast to the control group. Specifically, students in the experimental group showed noticeable progress in terms of fluency and accuracy when speaking in English. This improvement was accompanied by increased levels of confidence and engagement during oral communication activities. The findings of this study suggest that the monologue technique is an effective instructional strategy for improving speaking skills in English. It helps students become more articulate and confident in their language use, making it a valuable addition to English language teaching practices in secondary schools.